1991
DOI: 10.1002/bip.360310502
|View full text |Cite
|
Sign up to set email alerts
|

Differential scanning calorimetry studies of NaCl effect on the inverse temperature transition of some elastin‐based polytetra‐, polypenta‐, and polynonapeptides

Abstract: Differential scanning calorimetry studies of the effect of NaCl on protein-based polymer self-assembly has been carried out on six elastin-based synthetic sequential polypeptides--i.e., the polypentapeptide (L-Val1-L-Pro2-Gly3-L-Val4-Gly5)n and its more hydrophobic analogues (L-Leu1-L-Pro2-Gly3-L-Val4-Gly5)n and (L-Val1-L-Pro2-L-Ala3-L-Val4-Gly5)n; the polytetrapeptide (L-Val1-L-Pro2-Gly3-Gly4)n and its more hydrophobic analogue (L-Ile1-L-Pro2-Gly3-Gly4)n; and the polynonapeptide (a pentatetra hybrid), (L-Val1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 44 publications
10
84
0
1
Order By: Relevance
“…1 Recently, elastin-derived polypeptides, represented by (VPGVG) n , have attracted much attention due to their potential uses in energy conversions, 2 as control-release drugs, 3 designing artificial vascular tissue, 4 and as building blocks for elastic biomolecular machines. 5 For example, Urry and co-workers have shown that one can modulate the transition temperature of a given elastin polymer by many physicochemical changes, such as pH, 6 pressure, 7 salt, 8 organic solutes, 6 and the oxidation state of a side-chain functional group. 5 Chilkoti and co-workers have devised a new way to thermally target polymer-drug conjugates to solid tumors, by exploiting the phase transition-induced aggregation of elastin-like polypeptides.…”
Section: Introductionmentioning
confidence: 98%
“…1 Recently, elastin-derived polypeptides, represented by (VPGVG) n , have attracted much attention due to their potential uses in energy conversions, 2 as control-release drugs, 3 designing artificial vascular tissue, 4 and as building blocks for elastic biomolecular machines. 5 For example, Urry and co-workers have shown that one can modulate the transition temperature of a given elastin polymer by many physicochemical changes, such as pH, 6 pressure, 7 salt, 8 organic solutes, 6 and the oxidation state of a side-chain functional group. 5 Chilkoti and co-workers have devised a new way to thermally target polymer-drug conjugates to solid tumors, by exploiting the phase transition-induced aggregation of elastin-like polypeptides.…”
Section: Introductionmentioning
confidence: 98%
“…The inverse phase transition of ELPs can also be isothermally triggered by depressing their T t below solution temperature by the addition of kosmotropes from the Hofmeister series. [8][9][10][11] At the molecular design level, the T t of an ELP can be tuned by two orthogonal parameters: the identity and mole fraction of the ''guest'' residue in the fourth position (Xaa), and the chain length of the ELP; recombinant synthesis provides complete control over these two variables, so that its is possible to synthesize ELPs with exquisite control of their T t , which is important for different applications of these stimulus responsive polypeptides. 12,13 We discovered that the phase transition behavior of ELPs is retained when ELPs are fused to soluble proteins, 1 and we exploited this observation to develop a non-chromatographic method-ITC-for purification of recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…4). 101 Adding salts usually lowers the solubility of ELPs 91,102 according to the Hofmeister series, providing the opportunity to use ELP tags in nonchromatography protein purification by using inverse transition cycling. 103 Similar to synthetic polymers exhibiting LCST and consistent with the Flory-Huggins theory of polymer solutions, ELPs with a larger molecular weight have a lower T t .…”
Section: Amorphous Artificially Engineered Protein Gelsmentioning
confidence: 99%